PENGARUH KREDIT BANK KEPADA SEKTOR SWASTA, KREDIT BANK KEPADA SEKTOR PEMERINTAH, SERTA KURS TERHADAP NERACA TRANSAKSI BERJALAN DI NEGARA-NEGARA ASEAN - Rauzatul Jannah; Taufiq Carnegie Dawood; Rustam Effendi; Muhammad Ilhamsyah Siregar; Muhammad Abrar; Cut Zakia Rizki (Jurnal Ekonomi dan Kebijakan Publik Indonesia, 2022)
This study aims to examine the effect of bank credit for the government sector, bank credit for the private sector, and exchange rate on current account balance in ASEAN countries. This type of research is a quantitative descriptive study with the Random Effect EGLS panel data method. The data used are secondary data, obtained from the World Bank, FRED, and CEIC from 1990-2019. The results of this study indicate that exchange rate have a positive and significant effect on current account balance in ASEAN countries. Similarly, bank credit for the government sector, have a positive and significant effect on the current account balance. In addition, private sector bank credit, have a positive impact on the current account balance.